55 Evaluation of Potential Clinical Response and Cardiovascular Outcomes Predictors in a Tertiary Cardiac Resynchronisation Therapy Implantation Centre. (3rd June 2016) - McAloon, Christopher; Heining, Dominic; Atherton, Gavin; Anderson, Benjamin; Randeva, Harpal; O'Hare, Paul; Osman, Faizel
Abstract : Background: Cardiac Resynchronisation Therapy (CRT) is an effective treatment for dys-synchronous chronic heart failure (CHF), however there is a significant non-response rate. Clinic predictors of response and cardiovascular outcome are often inconsistently reported. The aim of the study was to examine previously reported clinical predictors of response and cardiovascular outcomes in a heterogeneous CHF patients undergoing CRT implantation at a UK tertiary centre. Methods: A retrospective single-centre cohort study of all consecutive CRT implantations (147 (49.0%) CRT-p; 153 (51.0%) CRT-d) performed over 5 years (Jan 2009–Dec 2013). Implants had to meet eligibility criteria; successful implant, follow-up case records availability and clinical response determination. Clinical response was defined by three independent reviewers as a New York Heart Association classification symptom reduction > 1 class or class I maintenance from pre-implant to the most recent cardiology/heart failure consultation. Major Adverse Cardiovascular Events (MACE), defined as all-cause mortality or first heart failure hospital admission, was recorded independently of clinical response. Pre-identified potential clinical predictors (Table 1 ) were analysed to determine ability to predict response and MACE. Results: A cohort of 300 (mean age 71.5 years ± 10.1; 227 (75.7%) males) had clinical response definable (158 (52.7%) responders; 142 (47.3%) non-responders) at a median of 12.0 ( ± (IQR) 4.38–25.5) months. Baseline cohort characteristics were: 171 (59.0%) ischaemic aetiology; 72 (28.0%) AF; 75 (25.9%) Diabetes; 103 (25.3%) Chronic Kidney Disease (CKD); Electrocardiogram: QRS 154mesc (± 144–172); 186 (71.8%) LBBB; Echocardiogram 24.1% (± (SD)8.3) LVEF. Multivariate logistic regression (Table 1) of pre-defined parameters of overall clinical response demonstrated increasing age at implant predicted a poorer response (OR 0.96, p 0.002, CI (95%) 0.94–0.99). CKD status trended towards predicting long-term (>12 weeks) clinical response (OR 0.58, p 0.06, CI (95%) 0.33–1.01). Figure 1 shows the survival curve demonstrating significantly higher all-cause mortality rate for those with CKD at implant ( p < 0.001). Multivariate Cox regression demonstrated that CKD status predicted increased MACE (HR 2.10, p0.001, CI (95%) 1.23–3.19) and all-cause mortality (HR 2.06, p < 0.007, CI (95%) 1.22–3.46) following CRT implantation. Conclusion: Increasing age at implant predicts poorer overall clinical response. CKD status predicts increased MACE and all-cause mortality events following CRT.